Is There a Diabetes–Kidney–Heart Continuum? Perspectives From the Results of the Cardiovascular and Renal Outcome Clinical Trials With SGLT2 Inhibitors - Bao, Liwen; Gao, Xiufang; Xie, Kun; Li, Yong (Frontiers in Cardiovascular Medicine, 2021)
Heart failure is associated with a substantial risk of mortality and morbidity. Findings from recent cardiovascular outcome trials have shown promise for sodium-glucose cotransporter-2 (SGLT2) inhibitors in preventing heart failure in patients with type 2 diabetes mellitus (T2DM). Notably, the benefits of SGLT2 inhibitors were consistent despite the presence of risk factors like atherosclerosis. Increasing evidence suggests that SGLT2 inhibitors may confer their cardioprotective effects through multiple mechanisms, ranging from improving cardiac and vascular performance to metabolism. The reduction of heart failure risk by SGLT2 inhibitors may also be attributed to the preservation of renal function. Indeed, renal insufficiency is a frequent comorbidity of patients with heart failure and T2DM; hence, the natriuretic and kidney protective effects offered by SGLT2 inhibitors may contribute to limiting adverse cardiac outcomes. In this article, we discuss the latest findings from the cardiovascular and renal outcome trials, paying special attention to the interlink between heart and kidney function, and how effective treatment of heart failure—irrespective of T2DM diagnosis—may require agents that offer both cardiac and renal protection.